Publisher Correction: Internalized TSH receptors en route to the TGN induce local Gs-protein signaling and gene transcription - Amod Godbole (Nature Portfolio, 2018)
The original version of this Article contained errors in the three equations reported in the Methods section entitled ‘Statistics’, as described in the accompanying Publisher Correction. These errors have been corrected in both the PDF and HTML versions of the article.